2009
DOI: 10.1111/j.1365-3040.2009.02025.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis ofβ‐aminobutyric acid priming and abscisic acid – induction of drought resistance in crabapple (Malus pumila): effect on general metabolism, the phenylpropanoid pathway and cell wall enzymes

Abstract: In a variety of herbaceous, model and crop plants, DL-baminobutyric acid (BABA), has been shown to enhance both biotic and abiotic stress resistance by potentiating rather than inducing resistance responses but studies in woody plants are lacking. In the present study, twodimensional difference in-gel electrophoresis (DIGE) was used to quantify differences in protein abundance in leaf tissue from BABA-treated, abscisic acid (ABA)-treated and untreated (control) plants during a 10 d drought stress. ABA-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 86 publications
1
39
0
Order By: Relevance
“…An increased sensitivity to drought has been observed in some pectin defective mutants such as qua1 with their decreased HG content (Bouton 2002). Several PME isoforms are transcriptionally upregulated in crab apples (Malus pumila) under drought conditions after drought tolerance has been induced through application of DL-b-aminobutyric acid (Macarisin et al 2009). The influence of pectin content and DM on drought sensitivity could be due to the effect of pectin on the water retention potential of the cell walls, and/or interactions of the pectin matrix with the cuticle, as a defective cuticle would lead to increased water loss through evaporation.…”
Section: Abiotic Interactionsmentioning
confidence: 98%
“…An increased sensitivity to drought has been observed in some pectin defective mutants such as qua1 with their decreased HG content (Bouton 2002). Several PME isoforms are transcriptionally upregulated in crab apples (Malus pumila) under drought conditions after drought tolerance has been induced through application of DL-b-aminobutyric acid (Macarisin et al 2009). The influence of pectin content and DM on drought sensitivity could be due to the effect of pectin on the water retention potential of the cell walls, and/or interactions of the pectin matrix with the cuticle, as a defective cuticle would lead to increased water loss through evaporation.…”
Section: Abiotic Interactionsmentioning
confidence: 98%
“…Some quemical inducers are 2,6-dichloro isonicotinic acid (INA), benzo-(1,2,3)-thiadiazole-7-carbotionic acid S-methyl ester (BTH), β-aminobutyric acid (BABA) (Oostendorp et al, 2001;Conrath et al, 2002) and hexanoic acid, which by root treatment protects tomato plants and Arabidopsis against Botrytis cinerea (Vicedo et al, 2009;Kravchuk et al, 2011). Regarding abitotic stress, BABA has been shown to confer plant protection against salinity and drought (Jakab et al, 2005;Macarisin et al, 2009). Moreover, stress can also boost plant stress tolerance through induction of acclimation responses.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown the efficacy of BABA against Xanthomonas citri in key lime but the implication of PR proteins is unclear (Beheshti et al, 2011). In crabapple (Malus pumila Mill), BABA induced drought stress resistance by potentiating abscisic acid (ABA) pathway and several ABA-independent responses, such as changes in cell wall enzymes and a suppression of lignin (Macarisin et al, 2009). …”
Section: Synthetic Resistance Inducersmentioning
confidence: 99%